1997
DOI: 10.1046/j.1365-2141.1997.d01-2073.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic study of 30 patients with multiple myeloma: comparison of 3 and 6 day bone marrow cultures stimulated or not with cytokines by using a miniaturized karyotypic method

Abstract: Summary. Cytogenetics in multiple myeloma (MM) cases are generally difficult to perform due to the low proliferation index of malignant plasma cells (PC) in most cases. Although IL-6 and GM-CSF stimulate the in vitro proliferation of malignant plasma cells, their usefulness for improving cytogenetic results in multiple myeloma patients remains questionable, because results which compare various culture conditions in a sufficient number of patients are not available. By using a miniaturized karyotypic method, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
6
23
2
Order By: Relevance
“…2,4,[17][18][19] A number of techniques have been investigated in order to increase the detection rate of abnormal clones; [2][3][4][5][6] nevertheless, a large number of normal karyotypes are still reported, mainly in smoldering diseases. 20 When only normal metaphases are identified, it has been shown that they originate from the normal hematopoietic component 2 and additional techniques, such as flow cytometry or interphase fluorescence in situ hybridization are able to detect genomic defects in almost all patients whatever the stage of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,[17][18][19] A number of techniques have been investigated in order to increase the detection rate of abnormal clones; [2][3][4][5][6] nevertheless, a large number of normal karyotypes are still reported, mainly in smoldering diseases. 20 When only normal metaphases are identified, it has been shown that they originate from the normal hematopoietic component 2 and additional techniques, such as flow cytometry or interphase fluorescence in situ hybridization are able to detect genomic defects in almost all patients whatever the stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Multiple myeloma (MM) is a B cell neoplasia characterized by the expansion of a malignant plasma cell population within bone marrow, often associated with a low mitotic index leading to difficulties in the cytogenetic detection of the malignant clone. [2][3][4][5][6] On a morphological and phenotypic basis, MM is considered as a unique but heterogeneous disease. [7][8][9] We report the cytogenetic results obtained in a series of 81 MM patients with abnormal karyotypes showing the presence of two different cytogenetic patterns and leading to the evidence that among MM patients with abnormal karyotypes, at least two groups with a different prognosis can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Eight large published series have been reviewed constituting 173 hyperdiploid karyotypes. 5,7,[14][15][16][17][18][19] The most frequently gained chromosomes were chromosomes 9 (156/173), 15 We then examined what would be the most sensitive and specific combination of three probes for the detection of hyperdiploidy. The analysis showed that the combination of chromosomes 5, 9, and 15 is the best compromise between specificity and sensitivity.…”
Section: Probe Selectionmentioning
confidence: 99%
“…35 The remaining four reported cases showed the derived chromosome 11 as the unbalanced form of the translocation in association with other abnormalities, B-ALL (one case), 36 MDS (two cases) 37,38 and multiple myeloma (MM) (1 case). 39 4. Abnormalities of chromosome 5: t(5;11)(q31;q23): Two cases in the Workshop had a translocation involving 11q23 with 5q31, t(5;11)(q31;q23).…”
Section: A Overall Cases In 'Other' Groupmentioning
confidence: 99%